COVID-19 Pandemic and South Korean Higher Education: A Threat with a Silver Lining? - Hong, Bawool (International Higher Education, 2020)
COVID-19 is an inescapable pandemic that is posing unprecedented threats to higher education communities all around the world, especially in South Korea, one of the countries most heavily affected in Asia. However, universities and policy makers have a choice in terms of how to view this outbreak: solely as a threat, or also as an opportunity to take in longer-term lessons in managing internationalization and student mobility, and adequately utilizing online delivery and educational technologies.